Changes in peripheral blood lymphocyte subsets during arthritis development in arthralgia patients. Issue 1 (December 2016) - Lübbers, Joyce; van Beers-Tas, Marian; Vosslamber, Saskia; Turk, Samina; de Ridder, Sander; Mantel, Elise; Wesseling, John; Reijm, Martine; van Hoogstraten, Ingrid; Bijlsma, Johannes; van Schaardenburg, Dirkjan; Bontkes, Hetty; et al.
Abstract Background Multiple lymphocyte subsets like T and B cells have been connected to joint infiltration and inflammation in rheumatoid arthritis (RA). Identification of leucocyte subsets that are dysregulated in arthritis development could provide insight into the aetiology of RA. This study aimed to investigate the composition of the peripheral blood components, i.e. CD14+ monocytes, CD4+ and CD8+ T lymphocytes (CD3+ ), CD80+, C-X-C chemokine receptor 3 (CXCR3)+ and CD27+ B lymphocytes (CD19+ ), CD16+ CD56+ CD3− natural killer (NK) cells and activated CD56+ CD3+ T cells, for association with arthritis development in patients with arthralgia. Methods Peripheral blood was collected from 89 patients with early RA (disease duration <6 months), 37 healthy controls (HC) and 113 patients with arthralgia (22 developed arthritis within ≤1 year, 18 developed arthritis after >1 year and 73 did not develop arthritis). Absolute numbers of monocytes and lymphocyte subsets in whole heparinized blood were determined with flow cytometry using quantification beads in combination with fluorescent labelled antibodies for T cells, B cells, monocytes, NK cells and activated T cells. Results In patients with early RA, significant decreases in numbers of (activated) T cells, CD80+ and memory B cells and a trend towards smaller numbers of CD8+ T cells was observed compared to HC. Similar differences were seen in patients with arthralgia who developed or did not develop arthritis (non-converters), with significantly decreased CD8+ T cells and memory B cells. Patients with arthralgia who developed arthritis were split into groups that developed arthritis within 1 year (early converters) or after 1 year (late converters). Late converters had a significantly decreased number of CD8+ T cells compared to non-converters; early converters had a decreased number of memory B cells. Longitudinal analysis of converters showed a significant relative increase in CD80+ B cells towards the conversion time point compared to 24 months prior to conversion. Conclusions This study revealed that patients with arthralgia who develop arthritis demonstrate a change in cellular immune parameters apparent in the periphery, starting with a decrease in cytotoxic T cells 24 months prior to arthritis development, followed by a decrease in the number of memory B cells 12 months prior to disease onset.